2004
DOI: 10.3171/foc.2004.17.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation in patients with spinal infection

Abstract: Object Placement of instrumentation in the setting of a spinal infection has always been controversial. Although the use of allograft and autograft bone has been accepted as safe, demonstrations of the effectiveness of titanium have been speculative, based on several retrospective reviews. The authors' goal in this study was to demonstrate the effectiveness of instrumentation in the setting of a spinal infection by retrospectively reviewing their cases over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 48 publications
3
75
0
Order By: Relevance
“…The advocates for spinal instrumentation argued that stabilization of the spine is very important for the suppression and eventual elimination of infections [13,14]. Increasing evidence has also showed that instrumentation in the presence of active infection is well tolerated while spinal stability is maintained effectively with sufficient restoration of sagittal alignment of the spine and relatively shorter duration of bed rest [3,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The advocates for spinal instrumentation argued that stabilization of the spine is very important for the suppression and eventual elimination of infections [13,14]. Increasing evidence has also showed that instrumentation in the presence of active infection is well tolerated while spinal stability is maintained effectively with sufficient restoration of sagittal alignment of the spine and relatively shorter duration of bed rest [3,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium offered the benefits of superior corrosion resistance, biocompatibility, resistance to glycocalyx formation, and reduced MRI artifact compared with stainless steel. 9 However, when comparing the mechanical properties of titanium to stainless steel, there is a reduction in stiffness, resistance to notch effects, and tolerance to cyclic loading. Thus, many surgeons still prefer stainless steel implants for long-segment or spinal deformity surgeries.…”
mentioning
confidence: 99%
“…This is true for the thoraco-lumbar region [7,14,16,18,19,24], as well as for the cervical spine [15][16][17]24]. Furthermore, a direct comparison between autologous iliac bone strut and cages did not show a difference in clinical and imaging outcomes [22].…”
Section: Discussionmentioning
confidence: 93%
“…Safe use of expandable titanium cages has been demonstrated for the thoraco-lumbar region [18,19], but has not been reported yet in detail for the cervical spondylitic spine. Figures depicting the use of expandable cages in cervical vertebral body replacement are given in the papers published by Lee [17] and Acosta [1] in 2004 without going into details.…”
Section: Discussionmentioning
confidence: 99%